The Strategy of Coastal Eco-Tourism Based on Cultural Ecosystem Services Approach: A Case Study in Ciletuh Bay - Eka Yudhistira; Tridoyo Kusumastanto; Luky Adrianto; Fredinan Yulianda (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Ciletuh Bay has a natural magnificence that attracts local and foreign tourists. Tourist interest was reflected by the many visits demanding the government manage it properly to achieve social, economic, and ecological sustainability. Research on the assessment of cultural ecosystem services in Ciletuh Bay has not been carried out. At the same time, this is necessary for policymakers to maintain sustainable Ciletuh Bay coastal ecotourism. This study aims to estimate the value of cultural ecosystem services in Ciletuh Bay in two ways. The first method is assessing the balance of supply and demand for cultural ecosystem services that adopt the Burkhard Model, namely through individual preferences for the beauty of several types of landscapes in Ciletuh Bay. The second assessment is an economic valuation using the travel cost method (TCM). The results showed that the balance of supply and demand for cultural ecosystem services in Ciletuh Bay contained several types of landscapes in unstable conditions. The economic value of Ciletuh Bay coastal ecotourism is IDR 862,640,124,311.00/year or IDR 77,911,861.00/ha/year.